Developing critical thinking among children and bibliotherapy in the library - Bišćan, Frida (Knjižnica, 2023)
Purpose: The paper aims to point out the possibilities of developing critical thinking in children by conducting bibliotherapy workshops in the library, based on the template of a traditional children’s story. The work is based on a course, which the authors run at the Croatian Training Centre for Continuing Education of Librarians to encourage critical thinking in children, develop reading habits and create a critical reader. It is based on the workshops that were an integral part of the international project TRACE.Approach/methodology: The paper presents the workshops the authors conducted as part of the Erasmus+ project Traditional children’s stories for a common future – TRACE. The workshops are shared with the librarians through the Croatian Training Centre for Continuing Education of Librarians. We encourage children to think and create their own opinions using different methods, most of which are based on the modernized Socratic method. Results: Children often do not get to express their opinions by questioning their attitudes. The conducted workshops showed how it is possible to use stories with different ethical themes to stimulate critical thinking in children and teach them how to be ac-tive participants in their society. Practical use: Considering the possibility of using/combining several methods and conducting workshops in “continuations”, it is possible to apply them both in school libraries and children’s departments of public libraries. Originality and value: The paper points to the importance of developing critical thinking in children and highlights the value of traditional stories that influence children’s awareness of their personality and shaping of their attitudes, contributing to the ability to solve life’s problems and the development of a value system and the improvement of interpersonal relationships.
Keywords: biblioterapija; branje; Hrvaška; kritično mišljenje; otroci; splošne knjižnice